2012
DOI: 10.1590/s1415-43662012001100009
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade espacial de atributos físicos e mecânicos de um Argissolo sob cultivo de cana-de-açúcar

Abstract: Propôs-se, neste trabalho, estudar a relação espacial de atributos físicos e mecânicos de um Argissolo Coeso cultivado com cana-de-açúcar. Estabeleceu-se um grid com 49 pontos georreferenciados para a retirada de amostras, em disposição 7 x 7, resultando uma malha de 120 x 120 m. As trincheiras foram abertas em duas camadas (0-20 e 20-40 cm) para a coleta das amostras deformadas e indeformadas. A distribuição normal foi verificada em todas as variáveis estudadas. Também se observou forte grau de dependência es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
2
3
0
6
Order By: Relevance
“…Thus, the pure nugget effect was observed for this property, due to the impossibility of fitting a semivariogram model to the distance scale used between the sampling points (Tavares et al, 2012). Anthropic interference, verified by successive croppings on this soil, adds sources of heterogeneity, promoting short distance variation, which may not be detected by the sampling grid.…”
Section: Results and Discusionmentioning
confidence: 96%
“…Thus, the pure nugget effect was observed for this property, due to the impossibility of fitting a semivariogram model to the distance scale used between the sampling points (Tavares et al, 2012). Anthropic interference, verified by successive croppings on this soil, adds sources of heterogeneity, promoting short distance variation, which may not be detected by the sampling grid.…”
Section: Results and Discusionmentioning
confidence: 96%
“…Conforme Carter (1990), quando o grau de compactação (GC) supera a faixa de 0,86 a 0,90 ocorre uma grande redução nos macroporos afetando os movimentos dos fluidos e diminuindo a capacidade de desenvolvimento dos vegetais. Tavares et al (2012) obtiveram, avaliando um Argissolo Coeso em Pernambuco cultivado com cana de açúcar valores de grau de compactação variando de 0,76 a 0,89.…”
Section: Resultsunclassified
“…The degree of spatial dependence (ADE) in all soil physical attributes, soil tillage and depth ranges were considered high (>75%), explained by the fact that the variables that present a strong degree of dependence are more influenced by intrinsic soil properties, such as texture, structure, organic matter content, density, mineralogy, and water content (Carneiro et al, 2009;Vendruscolo et al, 2011;Soares, 2013). Tavares et al (2012) evaluated the spatial relation of the soil density, porosity, macroporosity, microporosity and soil water content, verifying medium (27-75%) to high (>75%) degree of spatial dependence, for all evaluated attributes, indicating that these variables are non-random in space. The results of the variographic analysis showed that all physical attributes had spatial dependence (Figures 1 and 2).…”
Section: Resultsmentioning
confidence: 94%